The Pivotal Role of Boron in Improving the Azo Dye Degradation of Glassy Fe‐based Catalysts. Issue 3 (9th January 2020) - Xie, Shenghui; Xie, Yuelin; Kruzic, Jamie J.; Gu, Kunming; Yang, Haipeng; Deng, Yuanming; Zeng, Xierong
Abstract: Fe‐based metallic glasses have been confirmed to degrade azo dyes effectively, however, a detailed understanding, of the role of alloying elements and crystallization is still elusive. Herein, it is reported that boron‐facilitated hybrid structures greatly improve the degradation of methyl orange (MO) and the degrading rate can be further improved by 2.5 times after fully crystallization. Three distinct types of galvanic cells created by different iron‐containing phases are believed to dominate the degradation reactions. Most notably, some FeB‐based compounds precipitated from FeB‐based metallic glasses, such as Fe2 B, FeB and Fe5 SiB2, are found to have more negative electrode potential and higher catalytic efficiency than iron. These compounds create galvanic cells with α‐Fe and lose electrons, therefore promoting the degradation reaction. The favorable effects of the FeB‐based compounds are discussed at the light of their electron densities and energy band structures. These findings open a new research strategy to developing iron‐bearing catalysts for improved degradation of azo dyes. Abstract : Boron‐facilitated Fe‐based hybrid structures greatly improve the degradation of azo dyes. Three types of galvanic cells are deemed to dominate the degradation of Fe‐based alloys to dyes. Some Fe−B based compounds are found to have higher catalytic potential than Fe, which create galvanic cells with α‐Fe and therefore ensure a higher degradation ability to dyes.